The Use of Papaya Exudates for Fatty Acid Xilitol Synthesis - . Suhardi (Jurnal Teknologi dan Industri Pangan, 2003)
Fatty acid xylitol-ester (FAXILE) are xylitol esters of fatty acids with one to five DE (degree of esterification) value. FAXILE with DE value of 3 or higher can be used as low calorie fat replacer since they have low digestive property; while the xylitol ester with DE of less than 3 can be used as emulsifier. The FAXILE synthesis experiments were carried out by esterification of xylitol with palm oilÃ‚Â¡Ã‚Â¦s fatty acid (POFA) using papaya exudates as a lipase source. The objective of this experiment was to evaluate the potential of papaya exuadates for the synthesis of FAXILE. In this first experiment, test were carried out to determine hydrolytic activity of lipases obtained from different part of papaya plant. The test, were performed with the presence of CaO and under different pH value. The papaya exudates were used for FAXILE synthesis under an optimum condition obtained from the first experiment. Samples were drawn during incubation at 40Ã¢â‚¬Å¾aC for 1,2,3, and 4 days and hydroxyl number was analyzed to confirm the ester formation. The results showed that the most active exudate was from papaya leaves, followed by exudates from fruit with hydrolytic activity of 653 and 296 Ã†â€™ÃƒÂmol/g. minutes, respectively. The hydrolytic activity of the fruit exudate was optimum at pH 6.0, at 45-50Ã¢â‚¬Å¾aC, with the addition of CaO 4% dry exudates. The FAXILE synthesis with acid of papaya exudates was optimum at pH 6.0, at 45Ã¢â‚¬Å¾aC with molar ratio of xylitol: fatty acids was 1 to 6,3 days incubation. At this condition the conversion rate xylitol to FAXILE was 79%. Key words : Papaya exudates, ester of xylitol-fatty acid, FAXILE, POFA (Fatty acid xylitol ester)